2019
DOI: 10.3390/su11123388
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of Straw Bales as a Construction Material: A Review

Abstract: Straw bale buildings provide significant benefits in terms of costs, human health, and environmental sustainability. Several studies in different regions have underlined the remarkable properties of straw bales as insulating and construction material; however, to the authors’ knowledge, there are no reviews published on this topic. The main objective of this paper is to provide a better understanding of straw bale systems, focusing on durability and thermal and acoustic insulation properties. To this end, prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 43 publications
(75 reference statements)
0
28
0
12
Order By: Relevance
“…Numerous publications on straw bale construction have appeared in the literature [16]. Wei et al [17] developed a new thermal insulation material from rice straws with low density (200-350 kg/m 3 ), a thickness of 40 mm, and thermal conductivity around 0.051-0.053 W/(m•K) using high-frequency hot-pressing.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous publications on straw bale construction have appeared in the literature [16]. Wei et al [17] developed a new thermal insulation material from rice straws with low density (200-350 kg/m 3 ), a thickness of 40 mm, and thermal conductivity around 0.051-0.053 W/(m•K) using high-frequency hot-pressing.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lack of the data of straw bales in the software, the data are from existing researches. Considering the property differences of straw bales in different researches [40,50,51], the thermal conductivity of straw bale is designated as 0.700 W/mK. Existing researches confirmed the high thermal mass of straw bale walls [29,52] with specific thermal heat capacity ranging from 1388-2000 J/(kgK) [53,54].…”
Section: Iesve Simulation Processmentioning
confidence: 99%
“…Thirdly, straw-bale wall construction has excellent thermal insulation properties. Studies showed that the thermal insulation properties of straw bales and CLT walls are better than conventional wall constructions [46,47], including those of the masonry bricks that are widely used in rural residential buildings in China. Therefore, there is considerable potential to develop a bio-based building fabric with in-fill straw bales and structural timber frames for rural residential buildings in northeast China.…”
Section: Bio-based Building Fabricmentioning
confidence: 99%